1974
DOI: 10.1099/00221287-84-2-420
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Aspergillus nidulans Impaired in Penicillin Biosynthesis

Abstract: I N T R O D U C T I O NMutants blocked in the production of a metabolite can provide information on intermediate products in the biosynthetic pathway of that metabolite and the number of genetic loci involved. Lemke & Nash (I 972) have isolated mutant strains of Cephalosporium acremonium unable to yield P-lactam antibiotics and have reported on their ability to synthesize peptides implicated as intermediates in the elaboration of penicillin N and cephalosporin C.Bonner (1947) isolated 55 mutants of Penicillium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Also, mutant A. nidulans strains with altered ,-lactam-biosynthetic ability have been described (10) and characterized (20). The IPNS gene from a grampositive Streptomyces species is also of interest.…”
mentioning
confidence: 99%
“…Also, mutant A. nidulans strains with altered ,-lactam-biosynthetic ability have been described (10) and characterized (20). The IPNS gene from a grampositive Streptomyces species is also of interest.…”
mentioning
confidence: 99%
“…3A) and had wild-type morphology and conidiation. The mutation carried by this strain (described below) was designated npeE1 (npe, impaired in penicillin biosynthesis [14]; see Discussion). npeE1 is a temperature-sensitive mutation, the mutant phenotype being evident at 37ЊC but not at 25ЊC.…”
Section: Resultsmentioning
confidence: 99%
“…npeE1 defines a positive-acting regulatory gene of ipnA transcription essential for penicillin production. Mutations impairing penicillin biosynthesis have been already described for A. nidulans (14) and belong to four different complementation groups, denoted npeA, npeB, npeC, and npeD (11), none of which is located in chromosome IV (24), to which the npeE1 mutation has been assigned by haploidization analysis. Therefore, npeE1 identifies a new npe gene.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with Aspergillus nidulans where four complementation groups were identified (Edwards et al, 1974), the existence of a large group containing the majority of mutants was reported. This locus, designated npeA, has also been found to be affected in wild-type strains of Asp.…”
Section: Discussionmentioning
confidence: 99%
“…Complementation analysis with heterozygous diploids established the existence of two genetic loci. More recently, investigations of the genetics of penicillin production have been carried out in Aspergillus nidulans , and using mutants of this mould Edwards et al (1974) showed the presence of four genetic loci affecting penicillin synthesis.…”
Section: Introductionmentioning
confidence: 99%